1991
DOI: 10.1111/j.1365-2885.1991.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of antipyrine and sulphadimidine (sulfamethazine) in camels, sheep and goats

Abstract: The pharmacokinetics of antipyrine and sulphadimidine were studied in male camels, sheep and goats. The two drugs were administered concomitantly. Following intravenous injection of antipyrine (25 mg/kg) and sulphadimidine (sulfamethazine) (100 mg/kg), the pharmacokinetics of the two drugs were adequately described by a one-compartment model. Antipyrine half-life in goats (2.58 h) was shorter than that in sheep (4.04 h) and camels (18.78 h). The plasma clearance was greatest in goats then sheep and then camels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The present results corroborate these in vivo results, and are also in agreement with other kinetic data obtained from camels and goats given paracetamol (Ali et al., 1996b), sulphadimidine (Elsheikh et al., 1991), and metronidazole (Ali et al., 1999). In the paracetamol study, the kinetic differences between camels and goats were not limited to the slower clearance and longer half‐life of the drug in camels, but also extended to differences in the metabolic pathway of the drug in the two species.…”
Section: Discussionsupporting
confidence: 93%
“…The present results corroborate these in vivo results, and are also in agreement with other kinetic data obtained from camels and goats given paracetamol (Ali et al., 1996b), sulphadimidine (Elsheikh et al., 1991), and metronidazole (Ali et al., 1999). In the paracetamol study, the kinetic differences between camels and goats were not limited to the slower clearance and longer half‐life of the drug in camels, but also extended to differences in the metabolic pathway of the drug in the two species.…”
Section: Discussionsupporting
confidence: 93%
“…and variations in environmental conditions (Alvares et al, 1979). In this laboratory we have previously studied species differences between dromedary camels, desert sheep and Nubian goats with respect to drug metabolizing enzymes (Elsheikh et al, 1988;Elsheikh et al, 1991a) and in the pharmacokinetics of antipyrine and sulphadimidine (Elsheikh et al, 1991b). These studies have indicated that goats possess the highest and camels the lowest oxidative and conjugative enzyme activities in liver, kidney and duodenal mucosa.…”
mentioning
confidence: 99%
“…However, differences between these two species have been reported in the pharmacokinetics of some drugs, including antipyrine and sulphadimidine (Elsheikh et al, 1991), and CF (Danielson and Golsteyn, 1996;Uney and Traş, 2011) and in the activities of 7-methoxyresorufin O-dealkylase (MROD) and 6β-testosterone hydroxylase/17-testosterone oxidase, which are ascribed to CYP1A and CYP3A, respectively (Szotáková et al, 2004). In the present study, demethylation fractions of CF to PX and TP in goats were significantly different from those reported in sheep (0.12 and 0.72, respectively, Danielson and Golsteyn, 1996;0.08-0.20 and 0.61-0.78, respectively, Uney and Traş, 2011).…”
Section: Discussionmentioning
confidence: 98%